The Effects of the Real Exchange Rate on the Trade Balance: Is There A J-Curve For Vietnam? A VAR Approach - HOANG, Khieu Van (Asian Journal of Empirical Research, 2013)
This study employs a reduced-form VAR model to estimate trade balance’s responses to a positive shock to the real VND/USD exchange rate. For this purpose, we apply identification restrictions based on the conclusion by Krugman, Obstfeld and Melitz (2012), and on the theory of the AA-DD model to estimate the impulse response functions of the trade balance. We use a monthly data set of four endogenous variables and two exogenous variables from January 1995 to December 2012. Since the data of two endogenous variables is unavailable in monthly basis, we interpolate those series using Chow and Lin’s (1971) annualized approach from their annual series. Overall, we find that there exists a J-curve for Vietnam, and its effect lasts for 11 months. Particularly, the worsening effect on the trade balance becomes most severe in the third and the fourth months.